Using commercial contracts : a practical guide for engineers and project managers - Wright, David, 1939 November 11- (Chichester, West Sussex : Wiley Blackwell, 2016)
Using Commercial Contracts: a practical guide for engineers and project managers examines how the law of contract operates, and the way in which the legal system interprets what a contract actually means. By giving clear, readable and expert advice on key legal issues, this guide provides the manager and engineer with an easily understandable and practical approach to the laws of contract.
The law in general -- The start : using an agent -- The organisation -- Making the contract, part 1 : the requirements -- Making the contract, part 2 : offer and acceptance -- Words in contracts, part 1 : words used pre-contract -- Words in contracts, part 2 : post-contract -- The terms of the contract -- The basic framework : contracts of sale -- Liability exemption clauses -- Factors that may invalidate a contract -- Illegal contracts -- Privity of contract -- Other relationships -- Preliminary agreements and letters of intent -- How the contract ends -- Remedies for breach of contract and defences to claims.
Online resource; title from PDF title page (EBSCO, viewed July 6, 2016).
Includes index.
John Wiley and Sons
Keywords: Construction contracts -- England; Construction contracts -- Wales; LAW -- Military; Construction contracts; England; Wales